Financial management practices and performance of Zakat institutions in Malaysia - Anuar, Fatimah Sakeenah; Mohd Alwi, Norhayati; Mohd Ariffin, Noraini (Institut Perakaunan Negara, Jabatan Perakaunan Negara, 2019)
In Malaysia, critics have raised concerns over mismanagement and goal achievement in zakat institutions. In the light of this, zakat institutions have responded to these concerns by adopting greater transparency to show their accountability. This study examines the current financial management practices and performance in zakat institutions. Six elements of the Financial Management Accountability Index (FMAI), i.e. organisational management, budget, receipts, expenditures, assets and reporting, were used as a benchmark. The study also attempts to find a relationship between financial management practices and financial performance. It employed the census method where all 14 zakat institutions were enumerated, and a sample of 140 employees and 140 customers responded to performance questionnaires. Empirical data were collected mainly through three sets of questionnaires. The data were analysed using descriptive analysis and bivariate correlation. The findings show that receipts, disbursements and asset management are the most crucial areas reflecting a ‘good’ level of practice by zakat institutions. The results also show that there is a positive relationship between financial management and financial performance. This study is significant as it highlights areas for improvement and hence spurs the institutions to achieve their goal. The results may guide zakat institutions on the means to adopt greater transparency and accountability to the public in future.